Physiological disorders in fruits in arid region- A review (Indian Journal of Arid Horticulture, 2025)
Physiological disorder are distinguished from other disorders in that they are not caused by living organisms, but are caused by non- living, abiotic situations and cause a deviation from normal growth. Most of them are not reversible once they have occurred. The present review attempts to address this issue taking into account the fruit in general and fruits of arid region in particular.
Keywords: Physiological disorder; ber; pomegranate; bael; fig